Membangun Citra Destinasi melalui Kreativitas Visual: Workshop Fotografi Landscape di SMKN 7 Bandung - Wa Ode Seprina; Sarah Derma Ekaputri (Yayasan Literasi Sains Indonesia, 2024)
Formal education at Vocational High School (SMK) plays a crucial role as the final stage of secondary education, providing vocational education and skill training for students. The target partner of this Community Service activity is the students of SMKN 7 Kota Bandung, who face a lack of education in landscape photography, a skill increasingly in demand in the current digital era. The art of photography serves as a primary attraction, especially in the context of tourism that relies on visualization to enhance public interest. Students of SMKN 7 Bandung, representing the Generation Z as the nation's successors, play a crucial role as ambassadors of 'Wonderful Indonesia's tourism. In this era of information and technology, Generation Z has the potential to become the main drivers in promoting the natural beauty and cultural richness of Indonesia through photography. Through this workshop, it is expected that students, as Generation Z, can understand the importance of their role as tourism ambassadors. They are anticipated to harness their creative potential in landscape photography, utilizing social media as a platform to share the beauty of Indonesia's nature and cultural wealth. Thus, SMKN 7 Bandung becomes not only a center for vocational education but also a key pillar in shaping the image of 'Wonderful Indonesia' through the creative and innovative eyes of Generation Z.